The rise of Islamism and the future of Indonesian Islam - Al Qurtuby, Sumanto (Universiti Utara Malaysia Press, 2020)
Since the downfall of Suharto dictatorial regime in 1998, Indonesia has witnessed the upsurge of various Islamist groups that have in turn potentially threatened the countrys religious tolerance, civil Islam, and civic pluralism. While some have argued that the rise of these Islamist groupings could turn Indonesia into an intolerant Islamist country, this article argues that the Islamists will likely not be able to transform Indonesia into an Islamic State or Sharia based government and society, nor receive popular support and winning the heart of Indonesian Muslim majority because of the following fundamental reasons: the groups internal and inherent weaknesses, unsolid alliances among the groups, lack of Islamist political parties, limited intellectual grounds of the movement, the accommodation of some influential Muslim clerics and figures into the central government body, as well as public opposition to the Islamist groups.